The effect of reduced training volume during tapering on kicking response in taekwondo competitors - Carazo Vargas, Pedro (2017)
Purpose: The purpose of the study was to evaluate the effect of training volume during tapering on kicking performance in college Taekwondo competitors trained under a periodization block model. Methods: Participants were eight men and four women of the taekwondo team at the University of Costa Rica. All individuals completed a 13-week macrocycle loading phase (10 weeks of load and 3 weeks of taper). Following the loading phase, participants were paired by gender and randomly assigned to either a condition in which they kept the same training volume or a condition were training volume was reduced by 50% using a linear pattern. Kicking motion time was measured by instructing individuals to perform a circular kick to a target located at 1.10m high followed by another kick to a target located at 1.60m high. Kicking time response was obtained by recording the time required to kick a random sequence of 10 targets. The “Fitlight Trainer system” was used to time both dependent variables. Measurements were recorded at the beginning of the loading phase, the sixth week of the load period and twice a week during each of the three weeks of the tapering phase. Effect sizes (ES) were computed and analysis of variance (ANOVA) tests were used to detect significant interactions. Results: No significant interactions were found on kicking motion-time (Pre = 1.39 ± 0.09s vs. Post = 1.26 ± 0.06s) and kicking time response times (Pre = 9.63 ± 1.01s vs. Post = 8.47 ± 0.51s) in the group following the same training volume and the group with reduced training volume (Pre = 1.35 ± 0.10s vs. Post = 1.26 ± 0.11; Pre = 9.42 ± 1.52s vs. Post = 9.57 ± 1.78s, respectively). ANOVA results showed that regardless of the training volume, during the tapering phase improvements were observed on kicking motion time (p = 0.03) and kicking time response (p = 0.04), with the best performance observed at the end of the third week of the tapering phase. The 50% training volume reduction produced a higher ES on kicking motion time (1.50) and kicking time response (3.32) compared to no reduction in training volume (0.86 and 0.04, respectively). Conclusions: The reduction of volume training during tapering under a periodization block model improved kicking performance on taekwondo competitors. In the analyzed conditions, tapering must extend at least three weeks.